How can we create equitable access to hearing healthcare in Australia? Interview with Prof. Tom Calma, Prof. Kelvin Kong and Hon. A/Prof. Boe Rambaldini - Tom Calma; Kelvin M Kong; Boe Rambaldini (Sax Institute, 2021)
Despite decades of research demonstrating that early intervention is critical to diagnosing and treating ear disease in Aboriginal and Torres Strait Islander children, not enough progress has been made in providing culturally safe, accessible and equitable hearing health services. In the discussion below, Aboriginal and Torres Strait Islander health leaders Professor Tom Calma, Professor Kelvin Kong and Associate Professor Boe Rambaldini examine the problems and solutions for creating better services to meet the needs of communities where hearing health problems are being neglected, often with catastrophic results for Aboriginal and Torres Strait Islander children and their families.